Avaliação de indicadores de Transtorno de Déficit de Atenção e Hiperatividade e Ansiedade em adultos universitários - Krol, João Leon Silva (Brasil, 2024)
The attention deficit hyperactivity disorder is a pathology that appears in childhood and may continue to adulthood. It´s a group of difficulties in finding and maintaining concentration, carry out long activities, impulsiveness, inquietation, and so forth. The percentage of occurrence of it is increasing in world population and it is a predictor of suffering, because it is common for these people to experience difficulties adapting, especially with school demands. One of the comorbidities that was studied and is most common with this disorder is anxiety, which is an adaptive protective model that acts in dangerous situations. However, the people can lose the control of this model and suffer real harm to their well-being. The objective of this study was to collect data on the correlation of the presence of indices of attention deficit hyperactivity disorder and anxiety in 143 university students, using the following instruments: Adult Self-Report Scale (ASRS-18), the Hamilton Anxiety Rating Scale (HAM-A) and an authorial questionnaire based on the DSM-V to investigate the personal history of each participant. The validity and accuracy of the scales for the local public were also evaluated. The research was carried out with undergraduate university students at the Universidade Federal do Amazonas, regularly enrolled in units allocated in the city of Manaus. The results indicated that the group does not have ADHD according to the ASRS, with an average score of 2, corresponding to the item "Sometimes." The group's anxiety levels were considered mild, although 40% of the sample reported moderate and severe levels. The "other" gender category showed the highest level of attention deficit, while the female gender had the highest scores in hyperactivity and anxiety. The psychology course had the highest rates of inattention, hyperactivity, and anxiety among the courses with significant representation in the sample. A moderate correlation was found between Inattention and Hyperactivity, Inattention and Anxiety, and also between Anxiety and Hyperactivity. The data align with the research upon which the project is based. Strategies developed by students, as well as by families and educational institutions, are emphasized in order to address the issue. It is expected that the research will contribute with studies that focus on the themes presented, considering the specificities of the Amazon or Manauara regional context and promoting discussion to formulate strategies that help deal with the problem.